Mixed Sedimentation in the Transition Zone Between a Shallow-Water Delta and Tidal Flat and Its Influence on Reservoir Quality: A Case Study of Member B of the Asmari Formation in C Oilfield, South Iraq - Juan He; Li Yang; Yunjie Fan; Chen Hui; Bowen Zhang; Wen Zhou; Meiyan Fu (Applied Sciences)
The transition zone between a shallow-water delta and tidal flat is characterized by a high degree of mixed siliciclastic–carbonate sedimentation. There are frequent lateral and vertical variations in sandstone, dolostone, limestone, and mixed siliciclastic–carbonate rock (MSR); however, their influence on reservoir quality remains uncertain. Member B of the Asmari Formation (Asmari B) in Iraq’s C Oilfield was deposited in a remnant ocean basin formed by the closure of the Neo-Tethys Ocean. During the Oligocene–Miocene, frequent exposure of the Arabian Shield provided intermittent sediment sources to the study area. Under shallow water and relatively arid conditions, widespread mixed sedimentation of siliciclastic sand and dolomitic components occurred. Taking Asmari B as a case study, this research employs core and thin-section observations, trace element analyses, and quantitative mineralogical interpretations of logging data to investigate the characteristics of mixed sedimentation and to evaluate its impact on reservoir quality. Four key aspects were identified: (1) Four main types of mixed lithofacies developed in Member B of the Asmari Formation, namely sandstone-bearing dolomite, dolomitic sandstone, dolostone-bearing sand, and sandy dolostone. These lithofacies were deposited in the transition zone between distributary channels and intertidal zone with different water depths. As the terrigenous input decreased, the water depth for sand-bearing facies increased. In particular, sandy dolostone was predominantly formed in subtidal settings under the influence of storm events. (2) MSRs are categorized based on the proportion of the minor component into high and low mixing degrees. Based on mineral compositions interpreted from well logging data, the mixing degree of MSRs was characterized by the thickness ratio, using the thickness of high- and low-mixing-degree MSRs relative to the total thickness of the formation. The MSRs mainly developed in the B1, B2, B3-1, B3-2, and B4 sublayers, where moderate provenance supply facilitated the high mixing of terrigenous clastic and carbonate components. (3) The pore and throat patterns of MSR reservoirs change with the mixing degree index. When the dolomite content in sandstone exceeds 25%, the pore–throat structure changes significantly. A small amount of sand in dolostone has little effect on the pore and throat. Sandy dolostone exhibits the poorest reservoir quality. (4) Mixed sandstone reservoirs are distributed on both sides of the distributary channels and mouth bar. The dolostone-bearing sand reservoirs are distributed in the transition zone between the sandy flat and dolomite flat. Sandy dolostone is mainly thin and isolated due to the influence of storm events. This study provides guidance for understanding the development patterns of MSR reservoirs under similar geological settings, facilitating the next step of oil and gas exploration in these special reservoirs.